2010
DOI: 10.1177/154193121005400113
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Conflict Avoidance Responsibility Allocation on Pilot Workload in a Distributed Air Traffic Management System

Abstract: Pilot workload was examined during simulated flights requiring flight deck-based merging and spacing while avoiding weather. Pilots used flight deck tools to avoid convective weather and space behind a lead aircraft during an arrival into Louisville International airport. Three conflict avoidance management concepts were studied: pilot, controller or automation primarily responsible. A modified Air Traffic Workload Input Technique (ATWIT) metric showed highest workload during the approach phase of flight and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
2
1
Order By: Relevance
“…The present study failed to show a credible difference in subjective reports of workload, although overall the experimental group reported lower workload than the control group, in spite of credibly higher prefrontal blood oxygenation levels. One possible explanation is that subjective postrun workload ratings provide less reliable measures of workload than ratings gathered at fixed time intervals during task performance (Ligda et al, 2010). While fNIR recordings and time interval ratings can show the same trend in the data (Harrison et al, 2014), postrun ratings and fNIR measures might not correlate (as was the case in the present study).…”
Section: Discussioncontrasting
confidence: 49%
“…The present study failed to show a credible difference in subjective reports of workload, although overall the experimental group reported lower workload than the control group, in spite of credibly higher prefrontal blood oxygenation levels. One possible explanation is that subjective postrun workload ratings provide less reliable measures of workload than ratings gathered at fixed time intervals during task performance (Ligda et al, 2010). While fNIR recordings and time interval ratings can show the same trend in the data (Harrison et al, 2014), postrun ratings and fNIR measures might not correlate (as was the case in the present study).…”
Section: Discussioncontrasting
confidence: 49%
“…Pseudo-pilot stations were operated by awareness and workload probes administered at 3-minute intervals asked both pilots and controllers to subjectively rate their workload and answer descriptive questions about their situation awareness. The readers are referred to [18][19]21] for more details. …”
Section: Iiie Distributed and Networked Simulationmentioning
confidence: 99%
“…The results on pilot and controller situation awareness and workload have been reported in a number of papers [18,19,21] and will only be summarized here. In general, it was found that pilots had the highest situation awareness in Concept 1 (Pilot Primary), when they were most actively engaged in and responsible for separation assurance.…”
Section: Ivb Situation Awareness and Workloadmentioning
confidence: 99%